Glycemic index of nuggets made from eel flour (Monopterus albus) and tempeh flour for nutritional support for diabetic hemodialysis patients - Fery Lusviana Widiany (Ilmu Gizi Indonesia, 2019)
Background: Diabetes mellitus is one of the cause of end-stage renal failure and is also a comorbid of end-stage renal failure patient with hemodialysis. Diabetes is difficult to treat in diabetic hemodialysis patients. Diabetic hemodialysis patients will also experience malnutrition because of inadequate protein intake and gastrointestinal disorders such as nausea, vomiting, and anorexia, so nutritional support that meets the requirements of the diabetic hemodialysis diet is needed, which is high in protein, high in calcium, low in phosphorus, and has a low glycemic index, completed by nuggets made from a mixture of eel flour and tempeh flour. Objective: To determine the quantity and glycemic index category of nuggets made from a mixture of eel flour and tempeh flour with a proportion of 50%: 50% as nutritional support for diabetic hemodialysis patients. Methods: This experimental study using the one group intervention without control design used objects in the form of nuggets with the proportion of mixing eel flour (Monopterus albus) and tempeh flour by 50%: 50%. The measurement of glycemic index was carried out after respondents consumed test food (nuggets). Blood glucose levels measurement conducted at 30th minute, 60th minute, 90th minute, and 120th minute respectively. Results: The nugget’s glycemic index was 48.06, so it was categorized as a low glycemic index. Conclusion: Nugget made from eel flour and tempeh flour with a proportion of 50%: 50% is categorized as a food with low glycemic index, and it can be given as nutritional support for diabetic hemodialysis patients.